The Impact Of Scanning Technology And Shopping Convenience On Online Purchase Decisions With The Mediation Of Risk Perception - Ratna Puspita; Rizky Amalia; Oby Eko Purwanto; Bryan Givan (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This article explores the dynamic relationship between scanning technology, shopping convenience, risk perception, and online purchase decisions in the evolving landscape of e-commerce. Utilizing a sample of 60 individuals, the study employs Smart PLS analysis to investigate the direct and indirect effects of scanning technology and shopping convenience on consumer behavior, with risk perception acting as a mediator. The results reveal that scanning technology significantly influences risk perception and subsequently shapes online purchase decisions. While shopping convenience alone does not exhibit a statistically significant indirect effect, the study emphasizes the need for a comprehensive understanding of diverse factors impacting consumer choices. These findings provide valuable insights for businesses, such as PT. Dutagaruda Piranti Prima, to refine strategies and navigate the complexities of consumer behavior in the digital marketplace.